To Study the Organ Related to Artavavaha and Mutravaha Srotas with Their Applied Anatomy Mentioned in Ayurvedic and Modern Texts - Kumari, Nitu; Priyanka, Priyanka; Gupta, S.S. (Journal of Neonatal Surgery, 2025)
In Ayurvedic physiology, the concept of Srotas—intricate channels that facilitate the transport of various bodily substances—is fundamental to the understanding of human anatomy, physiology, and disease pathology. Two such significant Srotas are Ārtavavaha Srotas and Mutravaha Srotas, which are primarily responsible for reproductive and urinary functions, respectively. This review aims to critically evaluate the structural and functional attributes of these Srotas in light of classical Ayurvedic texts and correlate them with contemporary anatomical and physiological knowledge.The Ārtavavaha Srotas, which carry Ārtava (a term broadly encompassing menstrual blood and ovum), are described in Ayurveda as originating from the Garbhashaya (uterus) and Artavavaha Dhamanis (specific vessels). These structures show a strong anatomical correlation with the uterus, ovaries, and fallopian tubes in modern science, which are central to the female reproductive system. On the other hand, the Mutravaha Srotas, responsible for urine formation and excretion, are associated with the Basti (urinary bladder) and kidneys. Modern anatomical parallels can be drawn with the renal system, including the kidneys, ureters, bladder, and urethra.This integrative review highlights the anatomical and clinical relevance of these Srotas, exploring their role in both health and disease. It also emphasizes the importance of understanding classical Ayurvedic descriptions in the context of modern medical science, thereby promoting interdisciplinary research and holistic approaches to reproductive and urinary health.